2021
DOI: 10.3390/ma14174791
|View full text |Cite
|
Sign up to set email alerts
|

Modified Grape Seeds: A Promising Alternative for Nitrate Removal from Water

Abstract: The aim of this work was to investigate grape seeds as a potential adsorbent for nitrate removal from water. Grape seeds were modified by quaternization and the applicability of the modified grape seeds (MGS) was evaluated in batch adsorption experiments. Fixed bed adsorption and regeneration studies were carried out to determine the regeneration capacity of MGS. The maximum adsorption capacity of 25.626 mg g−1 at native pH (6.3) for nitrate removal by MSG was comparable to that of the commercial anion exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Triethylamine-functionalized polystyrene microsphere 47.27 [37] Modified brewers' spent grain 24.16 [57] Modified grape seeds 27.47 [44] Modified hazelnut shells 26.51 This study…”
Section: Adsorbentmentioning
confidence: 98%
See 1 more Smart Citation
“…Triethylamine-functionalized polystyrene microsphere 47.27 [37] Modified brewers' spent grain 24.16 [57] Modified grape seeds 27.47 [44] Modified hazelnut shells 26.51 This study…”
Section: Adsorbentmentioning
confidence: 98%
“…Similar results were reported by Keränen et al [34] using modified pine sawdust and [43] who studied the adsorption of nitrate onto quaternary starch derivatives. In addition, Stjepanović et al [44] reported that ETM-modified grape seeds could be considered as an alternative for the commercial ion exchanger Relite A490. The lower percent removal from wastewater samples is to be expected and could be explained by the fact that such a complex matrix contains other ions, which prevent nitrates from adsorbing by competing for the same adsorption sites.…”
Section: Effect Of Contact Timementioning
confidence: 99%